Biodegradation of Used Synthetic Lubricating Oil by Brevundimonas diminuta AKL 1.6 - Basuki, Witono (Makara Journal of Science, 2017)
Illegal disposal of used lubricating oil is a serious hazard to the environment and public health. This study is aimed at examining the biodegradation process of used synthetic lubricant using local microorganism. Oil-degrading microorganism were obtained from sea water contaminated with used lubricating oil. Those that showed some growth activity in Bushnell-Haas media containing used synthetic lubricating oil as a sole carbon source were selected. Its single colony was then generated by performing the dilution and scratch technique in the isolation and purification process. By using 16s rDNA, a potential strain namely AKL 1.6, was identified as Brevundimonas diminuta. Gas chromatography analysis was performed before and after the biodegradation process of the used oil. As a result, B. diminuta AKL 1.6 was found to utilize used synthetic lubricating oil as the sole source of carbon and to degrade most of the hydrocarbon within the oil for 14 days. Thus, this particular microorganism has the potential to be the single microbe for bioremediation of sea water contaminated by lubricating oil.